Effect of HTL thickness on air processed CVD perovskite solar cells. (2021) - Ngqoloda, Siphelo; Arendse, Christopher J.; Muller, Theophillus F.; Cummings, Franscious R.; Oliphant, Clive
Abstract: Lead iodide (PbI2 ) thin films were grown and converted to methyl ammonium lead triiodide (MAPbI3 ) perovskites through a two-step chemical vapour deposition process, addressing the issue of stable and scalable synthesis of perovskites layers. High quality, stable under open air, large perovskite grains close to micrometre size with full surface coverage were realised after 60 min conversion from the pre-deposited PbI2 . The relationship between the PbI2 layer deposited in the first step and the converted perovskite is discussed. The performance of the planar perovskite device was investigated with different thicknesses of the hole transport layer under open air. The devices performed relatively poor with highest efficiency of 4.35% obtained when a thicker hole transport layer thickness used, which is attributed to protruding grains of perovskite film through the hole transport layer, thereby corroding the silver metal electrode.